Determinants of cash holdings: Analysis of Islamic and conventional banks in Indonesia - Syifa Rahmatika; Muamar Nur Kholid (Jurnal Ekonomi & Keuangan Islam, 2021)
Purpose – This research aims to investigate the effect of dividend payment, cash conversion cycle, corporate social responsibility (CSR) disclosure, and corporate governance, which are integrated with the independence and size of the board of commissioners, on cash holdings in the banking industry in Indonesia, both in the conventional and Islamic banks.Methodology – Samples in this research were selected using the purposive sampling technique with the criteria of conventional banks registered in the Indonesia Stock Exchange (ISE) and Islamic banks registered in the Financial Services Authority (FSA) that released annual reports and financial reports during 2014-2019. There were 17 conventional banks and 11 Islamic banks met the criteria. Data were analyzed using multiple linear regression through Statistical Product and Service Solutions (SPSS) software.Findings – This research reveals that the effect of CSR disclosure and size of the board of commissioners on cash holdings is different between Islamic and conventional banks. Meanwhile, other variables used in this research have no significant effect on cash holding value, both in conventional and Islamic banks.Research limitations – Related to the samples of conventional banks, this research only investigates the ones registered in the ISE, not all conventional banks in Indonesia.Originality – This research provides empirical data related to the determinants of cash holdings in Islamic and conventional banks, which was rarely investigated in the previous research. Moreover, this research also uses the most updated data, Islamic and conventional banks during 2014-2019